Indicadores de sustentabilidade agrícola: análise cientométrica e avaliação multidimensional na cultura do café conilon e pimenta do reino - Nascimento, Thais Almeida do (2023)
Among the Brazilian states, Espírito Santo stands out, the largest producer of conilon coffee and black pepper, which represent respectively 70% and 55% of national production. With crops concentrated in the north of the state, these are an important source of income and employment. However, the intensification of production under the scenario of climate instability and scarcity of natural resources, can be a threat to the longevity of activities. Therefore, the sustainability of crop production is essential, demanding an assessment of the environmental, social and economic conditions of the properties. However, despite the volume of published works, there is a need to analyze the significance of the theme and its application in research. Therefore, the first chapter of this research aimed to carry out a bibliometric analysis on the Web of Science, of the main studies, researchers, organizations and countries relevant to academic research on the assessment of agricultural sustainability. The search terms used were agricultural sustainability, sustainability assessment, performance analysis, farm level, small owner, environmental, economic and social. The results showed an exponential growth in searches over the past seven years. The design of indicators supported by multivariate statistical methods shows a tendency in the assessment of sustainability. Despite the notable number of national articles, studies carried out outside the Brazilian reality stood out, indicating the need for investments in research and strengthening of scientific cooperation. The objective of the second chapter was to propose a method of evaluating sustainability based on the definition of indicators that describe the economic, environmental and social aspects of the production of conilon coffee and black pepper in the northern region of the state of Espírito Santo. The research was carried out in the municipality of São Mateus/ES in 50 properties, data were collected through on-site interviews with producers of both cultures. It was found 62 variables that were standardized and submitted to exploratory analysis by descriptive statistics. Then Pearson's correlation analysis allowed the extraction of a matrix with 21 variables, where the sampling assumptions were validated by the Bartlett test at 5% of significance and the Kaiser criterion test, with this, principal component analysis was applied to reduce the variables into indicators. The sustainability indexes were obtained by the scores of each indicator incorporating the spatial attribute to the individuals. To compare the sustainability profile, percentile confidence intervals were constructed using the bootstrap method with 95% confidence. Finally, cluster analysis was performed based on the nonhierarchical classification method with the support of the k-means algorithm to group the properties according to the similarity of the respondents' responses. All analyzes were performed in R Studio. The methodology allowed the calculation of four indicators that met the sustainable principles. Economic performance was highly correlated with social principles. Structural factors influence the socioeconomic aspects of the region. Technical assistance is one of the main actions to promote crop productivity. The indicators determined in this study were adequate to measure the sustainability index of conilon coffee and black pepper properties in the north of the state of Espírito Santo.